Research on non-contact wet mateable connector for optical communication and power transmission - Duan, Zhiyong; Zhang, Yurui; Hu, Jiaqi; He, Bohao; Yang, Canjun (Frontiers in Marine Science, 2023)
At present, contact watertight connectors are commonly utilized for the connection between underwater electromechanical equipment and the seabed observation network. Such traditional watertight connectors are easy to be irreversibly worn when plugging and unplugging, however, they have complicated sealing structures and limited service life. This paper designs a Non-contact Wet Mateable connector for Optical Communication and Power Transmission (OCPT-NWMC), which is based on technology of Contactless Power Transmission (CLPT) and optical communication. Docking structure of the sockets and plugs are designed, facilitating Remotely Operated Vehicle (ROV) to operate. A prototype of the OCPT-NWMC was established. The experimental results show that the connector designed can achieve 200W power transmission, with a maximum power transmission efficiency of 94%. The communication bandwidth reaches 18MHz. The OCPT-NWMC can assist the rapid and safe deployment and operation of seabed observation network.